ANALISIS PELAYANAN JASA PENGIRIMAN PAKET PADA PT. POS INDONESIA (PERSERO) PEKANBARU - Anggelia, Cherli; Zaili, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Service Analysis of Delivery Package at PT. Post of Indonesia (persero) Pekanbaru. In the case the researcher background by the phenomenon of customer complaints for its services delivery package at PT. Post of Indonesia (persero) Pekanbaru, so as to be able to compete in the business world oriented public servic, both goverment and private must be able to provide maximum satisfaction in terms of servic to its customers by providing a range of offers and ease of servic. This study is intended to know the implementation of services in the provision of postal services package at PT. Post of Indonesia (persero) Pekanbaru and barriers that constrain services in the provision of postal service package. As for the benefits that can be taken of the results this study are, first : in terms of the theoretical benefits is to develop and improve the ability ti think thraough the application of theory learned author. Secondly : in terms of practical benefits to increase the knowleadge of the author on the implementation of the package delivery services at PT. Post of Indonesia (persero) Pekanbaru, as consideration for the interest and input PT. Post of Indonesia (persero) Pekanbaru and parties who wish to pursue research related to the ame problem.Theory used in the this study is the theory of Philip Kotler about four determination that the provision of services reliability, responsiveness, assurance, emphaty and tangible. Methods used in this study is descriptive analysis of qualitative with obervation, interviews, and literature. Key informants were used in this study is service manager packagepost, staff of Pekanbaru post office, delivery post of Pekanbaru post office, and parcel post service user community. Researchers then developed with a snowball sampling method.Besed of the results of the research interviews, observation and literature, it can concluded thet the implementation of the postal parcel delivery services performing well but there are some thet are considered not optimal. There are still obstacles in the implementation. As for the obstacles that become obstacles in the implementation of the postal parcel servies at PT. Post of Indonesia (persero) Pekanbaru others limited human resources, lack of communication, and dependence with other parties. This has a majorJom FISIP Volume 1 No. 2 - Oktober 2014 2influence on the implementation of the package delivery services at PT. Post of Indonesia(persero) Pekanbaru.